Design, fabrication, and validation of ohmic heater to process green mussel meat. Issue 6 (23rd April 2021) - Rajasekaran, Bharathipriya; Subbiah, Balasundari; Stephen, Nimish Mol; Nagarajan, Muralidharan; Muniasamy, Satheesh
Abstract: A lab‐scale ohmic heater was designed and fabricated using stainless steel cylindroconical process chamber with one litre holding capacity fixed with a pair of titanium electrodes in the process chamber. The ohmic heater was validated by processing green mussel meat ( Perna viridis ) by varying voltage and duration of the heating process. Different voltages viz. 100 V and 120 V were attempted for process duration of 5 and 10 min. The processed mussel meat was tested for physical (cook loss), proximate (moisture, protein, fat, and ash), microbial (total plate count), and organoleptic (overall acceptability) quality to understand the effectiveness of ohmic heating to make the product safe for consumption. Based on the trial undertaken with mussel meat, ohmic heating at 120 voltage for 5 min was found suitable to process green mussel meat in terms of above mentioned quality attributes. Ohmic heater designed in this study could be an effective alternative to the conventional heating process in seafood processing. Practical applications: The conventional cooking methods such as steaming and boiling would lead to heterogeneous heating due to low rate of heat penetration which results in a reduction of yield whereas ohmic heating is reported to retain the nutrients without much loss. In this study, the ohmic heater was fabricated and validated for its potential for cooking green mussel meat. This study will support seafood industries to adopt ohmic heating for the thermal processing of seafood for better retention of valuable nutrients.